Abnormalities in ileal stem, neurogenin 3, and enteroendocrine cells in patients with irritable bowel syndrome - El-Salhy, Magdy; Gilja, Odd Helge (BMC gastroenterology, 2017)
This study examined whether the densities of stem- and enteroendocrine cell progenitors are abnormal in the ileum of patients with irritable bowel syndrome (IBS), and whether any abnormalities in ileal enteroendocrine cells are correlated with abnormalities in stem cells and enteroendocrine cell progenitors. One hundred and one IBS patients covering all IBS subtypes were recruited, and 39 non-IBS subjects were included as a control group. The patients and controls underwent standard colonoscopies, during which biopsy specimens were obtained from the ileum. The biopsy specimens were stained with hematoxylin-eosin and immunostained for Musashi-1 (Msi-1), neurogenin 3 (NEUROG3), chromogranin A (CgA), serotonin, peptide YY (PYY), oxyntomodulin (enteroglucagon), pancreatic polypeptide, and somatostatin. The immunoreactive cells were quantified by computerized image analysis. The densities of Msi-1, NEUROG3, CgA, and serotonin cells were reduced in all IBS patients and in patients with diarrhea-predominant IBS (IBS-D), mixed-diarrhea-and-constipation IBS (IBS-M), and constipation-predominant (IBS-C) relative to the control subjects. While the PYY cell density was increased in IBS-C relative to controls, it did not differ between control subjects and IBS-D and IBS-M patients. The densities of Msi-1 and NEUROG3 cells were strongly correlated with that of CgA cells. The abnormalities in the ileal enteroendocrine cells appear to be caused by two mechanisms: (1) decreases in the clonogenic activity of the stem cells and in the endocrine-cell progenitors differentiating into enteroendocrine cells, and (2) switching on the expression of PYY and switching off the expression of certain other hormones in other types of the enteroendocrine cells.